Scaling Agroclimatic Services: Reaching 810,000 farmers with Climate-Resilient Solutions across three Latin-American countries - Giraldo, Diana; Aye, Irma; Navarro, Carlos (2025)
Mainstreaming Local Technical Agroclimatic Committees (MTA, in Spanish) across Honduras, Guatemala, and Mexico has significantly enhanced agroclimate information dissemination, directly benefiting 214,000 farmers and indirectly reaching around 600,000 farmers through channels such as radio broadcasts and digital platforms. Strengthened institutional frameworks and strategic partnerships have facilitated the co-production and delivery of actionable climate data, helping farmers with informed decision-making for implementing climate-resilient agricultural practices. Sustained funding and policy commitments further reinforce the long-term impact of these initiatives.